Ethical decision-making in the work of project leaders - why ethics gains in importance in future project management - Agnes Wittrich (Business and Management '2022, The 12th International Scientific Conference "Business and Management", 12–13 May 2022 Vilnius, Lithuania, 2022)
The paper is a call for project practitioners of the future to educate their ethical perception, and for organizations to provide an appropriate environment which enables formation of ethical sensitivity. This theoretical study uses as method the systematic literature review to show that digital transformation impacts the ethical decision-making of project leaders of the future in the same way it contributes to the transformation of their profiles, the methods applied in their daily performance and the manner they conduct their projects. Teaching digital ethics, building digital skills, exercising practical application of ethical decision-making should be prioritized in future project management curricula by business and educational organizations.
Keywords: M140; M160; 330; Ethical decision-making; project management; digital transformation; digital ethics; ethical project leader